Mitigating Methane Emissions and Enhancing Rumen Microbial Diversity with Native Rumen Microbes Supplementation - AM, Mozart Nuzul Aprilliza; Miguel, Michelle; Son, A Rang; Lee, Sung Dae; Kim, Seon Ho; Lee, Sang Suk (Journal of Agriculture & Life Science, 2025)
The commercial feed additive, native rumen microbes (RC), derived from a diverse microbial community isolated from the rumen of Hanwoo steers is being explored to enhance rumen fermentation and improve ruminant feed utilization. This study evaluated the impact of native rumen microbes supplementation on methane emissions, microbial diversity, and fermentation efficiency on in vitro assessment. Treatments were as follows: CON (basal diet, without RC); T1 (basal diet + 0.1% RC); T2 (basal diet + 0.2% RC). Rumen fermentation parameters, total gas, and methane production were assessed at 12, 24, and 48 h of incubations. The in vitro gas production was carried out using the Ankom RF Gas Production System. Supplementation of RC significantly reduced the total gas production at 12, 24, and 48 hours of incubation (p < 0.05). Volatile fatty acid concentrations were increased, while acetate and propionate were decreased (p < 0.05) at 48 h by the supplementation of RC. Notably, the 0.1% inclusion level of RC significantly reduced methane production by 28.30% and 21.21% at 12 and 24 hours. Furthermore, microbial diversity analysis revealed significant shifts (p < 0.05) in bacterial composition between the control and treatment groups, while supplementation also promoted the growth of bacterial populations, such as Succiniclasticum. These findings suggest that native rumen microbes supplementation, particularly at 0.1% inclusion level, can enhance rumen microbial composition while significantly reducing methane production in vitro KCI Citation Count: 0